2022
DOI: 10.3390/ijerph19031412
|View full text |Cite
|
Sign up to set email alerts
|

Sprint Performance and Mechanical Force-Velocity Profile among Different Maturational Stages in Young Soccer Players

Abstract: The aim of the present study was to determine the influence of maturation status on the components of the sprint force-velocity (F-V) profile in young soccer players. Sixty-two young male soccer players from the same professional soccer academy took part in the present study. A cross-sectional design was implemented to compare the main components of the sprint F-V profile (i.e., maximal theoretical force (F0), velocity (V0), power (Pmax), and ratio of horizontal-to-resultant force (RFpeak), and decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…After that, biological maturity is identified as the time required to reach the adult stage. During this stage, several sexual, morphological, neural, hormonal, somatic, and skeletal changes may occur [ 12 , 13 ]. The predicted maturity offset is defined as the age at which the highest increase in height occurs.…”
Section: Introductionmentioning
confidence: 99%
“…After that, biological maturity is identified as the time required to reach the adult stage. During this stage, several sexual, morphological, neural, hormonal, somatic, and skeletal changes may occur [ 12 , 13 ]. The predicted maturity offset is defined as the age at which the highest increase in height occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the most decisive movements in soccer take place in areas smaller than 10 m 2 [14], high power locomotor activities such as sprinting can be the main factor factor in the sucess of high-level soccer performance [9][10][11]13]. Sprinting represents a multidimensional movement skill that involves an explosive concentric, and stretchshortening cycle (SSC) force production, using a number of lower-limb muscles [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In a one study, straight sprinting was observed to be the most frequent action before scoring goals for both striker and assist player in youth soccer player [20]. Biological maturity is identified as the time required to reach the adult stage and is characterized by the process of change in sexual, morphological, neural and hormonal, somatic, and skeletal factors [14,21]. Predicted maturity offset, defined as the age at which the greatest increase in height occurs (age at peak height velocity; PHV), is commonly used as an indicator of somatic maturity timing and status [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSS, also called maximal anaerobic speed, indicates the highest running speed achieved with maximum anaerobic energy release [ 9 ]. Since the decisive movements in soccer occur in small areas, PSS is essential in locomotor activities that require high power [ 13 , 14 ]. Moreover, a previous study conducted on young soccer players demonstrated that the most common movement before scoring a goal was sprinting [ 15 ].…”
Section: Introductionmentioning
confidence: 99%